Estudio de la adición de K+ y LiNbO3 en las propiedades finales del relaxor PMN procesado por mezcla de polvos - Cavalheiro, A. A. [UNESP]; Zaghete, M. A. [UNESP]; Cilense, M. [UNESP]; Villegas, M.; Fernandez, J. F.; Varela, José Arana [UNESP] (Elsevier, 2004)
PMN ceramic relaxor has been investigated by several researchers and many aspects of this material, like powder morphology, phase decomposition, weight loss during sintering process, densification, between others, still are investigated. PMN powder preparation has been shown more efficient when synthesized by columbite route, however lead addition stage for the PMN powder synthesis remains problematical. Therefore, this work proposes a new association of methodologies, using columbite route and the hydroxide precipitation method. Through use of the powder mixture technique, which permitted to obtain good green and sintered densities, was possible to observe K+ y Li + dopants reduce weight loss in sintering process and change significantly the dielectric properties. Addition of LiNbO3 seeds in conformation stage, which react in a distinct way as a function of the particle size, promotes the formation of differenced grains in the ceramic bulk. Consequently, very different dielectrics properties from conventional PMN ceramic were obtained.
Study of k and LiNbO3 addition on the final properties of the relaxor pmn processed by powder blend
Keywords: Microstructure; PMN; Processing and sinterization; Relaxor